Mutation Profiling in Haemophilia A - Oldenburg, J. (Thrombosis and Haemostasis, 2001)
Haemophilia A is a X-linked recessive bleeding disorder caused by deficiency or absence of coagulation factor VIII (FVIII) due to heterogeneous defects in the FVIII gene. The large size of the FVIII gene (26 exons spanning 186 kb) has hampered mutation analysis for many years. In 1991 the first systematic analysis of the complete coding region of the FVIII gene was performed by Higuchi et al. using Denaturing Gradient Gel Electrophoresis (DGGE) as a mutation screening method (1, 2). Notably, the causative mutation was not found in about half of the severely affected patients (1). This mystery was solved in 1993, when the intron 22 inversion was discovered (3, 4) that accounts for about 50% of the severe haemophilia A cases. The inversion mutation can be easily detected by Southern Blot. A recently described PCR-based method is more sophisticated, however once established, it allows rapid and convenient detection of the intron 22 inversion (5).